MODEL PENGEMBANGAN PEMBELAJARAN PAI BERBASIS LIVING VALUES EDUCATION (LVE) - Kasinyo Harto; Syarnubi Syarnubi (Tadrib: Jurnal Pendidikan Agama Islam, 2018)
In fact, the realistic-empirical data shows that the morality and character of the nation is now degraded, thus in itself inviting various calamities and disasters that extend to the social, religious, and political spheres, even in education. The general public indirectly blames educators from elementary to college, as the party most responsible for the deterioration of this nation in its mindset and behavior patterns that are inconsistent with the guidance of the world's citizens who should be cultured and dignified. Religious education in this case Islamic Education, hereinafter referred to as PAI, should be the basis of morality. But today it seems to have been seen as having lost its vital role in the effort to form the character of the nation's child morality. This is due to the fact that PAI learning practices have only been concerned only with cognitive aspects and ignored the fostering of affective aspects, namely the willingness and determination to practice the values ​​of religious teachings. This imbalance results in a gap between knowledge and experience, between theory and practice, or in the practice of religious education transformed into religious teaching, thus unable to form moral persons. As an effort of ijtihad to restore the essence, function and strategic role of learning of PAI in the formation of morals of the nation of this research is done with the principal of research problem, that is through improvement and development of PAI quality learning model for character formation of learners by using Living Values ​​Education paradigm. The purpose of this research is to design and formulate the learning model of PAI based on living values ​​education and how to implement it in learning process of PAI. Then, this research includes library research, therefore the steps that will be carried out is the exploration of some data from various literatures, both primary data, and secondary data. The method of collecting data is done by collecting books, articles, journals, scientific opinion in which to reveal and study living values ​​education, then look for writing about the learning of Islamic religious education. The data analysis technique using descriptive-analytic method. The data have been analyzed and then presented with deductive methods that depart from general theory to lead to the conclusion which is the answer of the research problem formulation.